Bluestockings, Feminists, or Women Workers? A Preliminary Look at Women’s Early Employment at the University of Toronto - Prentice, Alison (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1991)
AbstractOur knowledge of the unease generated by the presence of women in universities, exhibited by the use of terms like "bluestocking" or "feminist" to denigrate academic women, raises at least two questions about the early history of women who worked in Canadian universities. The first concerns such women's own image of themselves as academic workers; the second concerns the actual history of the movement of women into academic jobs. This paper begins an examination of the early employment of women at the University of Toronto. Outlining the structures of that employment over three periods ending in the 1940s, it also explores in a preliminary way how women's university work was perceived and experienced. Arguing that university employment remains gendered to this day, the paper calls not only for more research into its history, but also for a more politically conscious approach to the academic workplace, for greater equality for the female employees of universities, and for efforts to make universities less divisive and hierarchical workplaces altogether.